Advancing Research on Racial–Ethnic Health Disparities: Improving Measurement Equivalence in Studies with Diverse Samples - Landrine, Hope; Corral, Irma (Frontiers in Public Health, 2014)
To conduct meaningful, epidemiologic research on racial-ethnic health disparities, racial-ethnic samples must be rendered equivalent on other social status and contextual variables via statistical controls of those extraneous factors. The racial-ethnic groups also must be equally familiar with and have similar responses to the methods and measures used to collect health data, must have equal opportunity to participate in the research, and must be equally representative of their respective populations. In the absence of such measurement equivalence, studies of racial-ethnic health disparities are confounded by a plethora of unmeasured, uncontrolled correlates of race-ethnicity. Those correlates render the samples, methods, and measures incomparable across racial-ethnic groups, and diminish the ability to attribute health differences discovered to race-ethnicity versus to its correlates. This paper reviews the non-equivalent yet normative samples, methodologies and measures used in epidemiologic studies of racial-ethnic health disparities, and provides concrete suggestions for improving sample, method, and scalar measurement equivalence.